What Drives Gen Z to Buy? Unveiling the Role of Relationship Quality, Perceived Value, and Live Streaming Commerce in Developing Countries - Erobathriek, Annisya; Hasan, Djohan Gunawan; Jimmy, So Yohanes (Jurnal Multidisiplin Madani, 2024)
Continuing the pandemic's effect, there has been a notable shift towards online shopping driven by evolving consumer behavior, offering convenience in terms of accessibility, promotions, and direct interaction. Live streaming commerce has seen increased adoption as a result. The study extends the infancy research of live streaming commerce by aiming to develop a conceptual framework that links technological features and customer perceived value with customer relationship quality to influence purchase intentions for fostering economic growth. A total of 403 samples of Indonesian Gen Z were collected through a survey and analyzed using SmartPLS 3. Two main findings emerged. First, technological features significantly influence customers' perceived value (utilitarian, hedonic, social), which directly impacts purchase intention. Second, relationship quality as a mediating variable has a strong and significant impact on customer purchase intention based on the interaction effect of customers' perceived value, emphasizing relationship quality as a pivotal mediating variable. The novelty lies in integrating two exogenous variables, namely technological features and customer perceived value, with the variables of relationship quality and customer purchase intention. The findings provide theoretical and managerial implications for academics and practitioners